Phytochemical Screening and Antioxidant Activity of Strawberry Juice (Fragaria ananassa Duchessne) Against Ureum Level, Creatinin, and Enzyme Catalase Activity In Isoniazid-Induced Wistar Male Rats - Endang Sri Sunarsih; Ebta Narasukma Anggraeny; Patricia Sanggita Listyoputri Wibowo; Novi Elisa (Universitas STRADA Indonesia, 2020)
ROS increase can causes damage to the kidney so that urea and creatinine level increase in the blood and can be used as a marker of decreased kidney function. Excessive free radicals can cause a decrease in endogenous antioxidant activity, namely the catalase enzyme. This condition can be overcome by given exogenous antioxidants such as strawberry juice (Fragaria ananassa Duchessne). This study aimed to determine the effect of strawberry juice treatment against urea and creatinine levels in male Wistar rats Isoniazid-induced for 14 days divided into groups, namely normal control, negative control, positive control, strawberry juice dose of 3 g/kgBW, 6 g/ kgBW, and 9 g/kgBW. Data were collected on 1st, 15th, and 29th day. The results of the study concluded that strawberry juice had an effect in reducing levels of urea, creatinine and catalase enzyme activity in isoniazid-induced rats with an effective dose of 3g / kgBW